2015
DOI: 10.5152/tjg.2015.6339
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of alpha 1 antitrypsin deficiency in Iranian patients with neonatal cholestasis

Abstract: Background/Aims: There is little data concerning the incidence of alpha-1-antitrypsin"(AAT) deficiency, the most common genetic cause of liver disease, among children with neonatal cholestasis in Iran. Thus, this study was performed to analyze AAT deficiency in this group of patients. Materials and Methods: DNA samples from patients with neonatal cholestasis were investigated for Pi S and Pi Z alleles, using polymerase chain reaction-restriction fragment length polymorphism. Results: Thirty patients with neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The prevalence of A1ATD in newborns was 1/1,639 in USA and 1/1,575 (PiZZ genotype) in Sweden [9,10]. Conversely, the incidence of A1ATD has been reported to be very low in Iranian patients with neonatal cholestasis [11]. The incidence of this disease seems to be low in our country, Turkey, based on data from the pediatric transplantation center [12]; it was reported in 3.6% of infants with cholestasis [13].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of A1ATD in newborns was 1/1,639 in USA and 1/1,575 (PiZZ genotype) in Sweden [9,10]. Conversely, the incidence of A1ATD has been reported to be very low in Iranian patients with neonatal cholestasis [11]. The incidence of this disease seems to be low in our country, Turkey, based on data from the pediatric transplantation center [12]; it was reported in 3.6% of infants with cholestasis [13].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Iran, Lotfi et al (2005) used the PCR-RFLP and reported a very low incidence of homozygotes in patients with liver and pulmonary diseases (16). There are other studies which confirmed the absence of ATT deficiency in Iranian patients with cholestasis and jaundice (4,17,18). Our results are in accordance with previously published data from Iran, mentioning the low prevalence of AAT deficiency in infants with cholestatic idiopathic hepatic disease.…”
Section: Discussionmentioning
confidence: 82%